Proteolytic mapping of the coronavirus infectious bronchitis virus lb polyprotein: Evidence for the presence of four cleavage sites of the 3C-like proteinase and identification of two novel cleavage products - Liu, D.X. (2014)
10.1006/viro.1998.9199